2015
DOI: 10.1111/tan.12642
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐A‐B‐C‐DRB1‐DQB1 phased haplotypes in 124 Nigerian families indicate extreme HLA diversity and low linkage disequilibrium in Central‐West Africa

Abstract: The simultaneous typing of five-HLA loci at high resolution and the availability of pedigree data allowed us to characterize extended five-locus phased haplotypes in 124 Nigerian families and to compare the observed frequencies with those expected by an expectation-maximization algorithm for unphased data. Despite the occurrence of some frequent alleles at each locus (e.g. B*53:01, which is assumed to protect against Plasmodium falciparum), as many as 82% of the sampled individuals carry two unique five-locus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…). Interestingly, by sequencing the HLA‐C locus closely linked to HLA‐B (both loci being at about 95 kb and 0.2 cM from each other, Litwin, ) in all B*53‐positive individuals, we found that 34 of the 55 sequenced individuals (i.e., 62%) also carried the C*04:01:01:01 allele (Table ), although the amount of linkage disequilibrium across the HLA region appears to be low in Africa (Testi et al., ) compared to Europe (Bugawan, Klitz, Blair, & Erlich, ; Sanchez‐Mazas et al., ), as generally observed for other genetic markers (Campbell & Tishkoff, ). Therefore HLA‐B*53:01:01~C*04:01:01:01 (observed at the homozygous state in one GOU individual from Burkina Faso) appears as a putative haplotype associated with P. falciparum resistance.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…). Interestingly, by sequencing the HLA‐C locus closely linked to HLA‐B (both loci being at about 95 kb and 0.2 cM from each other, Litwin, ) in all B*53‐positive individuals, we found that 34 of the 55 sequenced individuals (i.e., 62%) also carried the C*04:01:01:01 allele (Table ), although the amount of linkage disequilibrium across the HLA region appears to be low in Africa (Testi et al., ) compared to Europe (Bugawan, Klitz, Blair, & Erlich, ; Sanchez‐Mazas et al., ), as generally observed for other genetic markers (Campbell & Tishkoff, ). Therefore HLA‐B*53:01:01~C*04:01:01:01 (observed at the homozygous state in one GOU individual from Burkina Faso) appears as a putative haplotype associated with P. falciparum resistance.…”
Section: Resultsmentioning
confidence: 80%
“…The data used in this study represent 484 individuals from 11 populations (Sudanese Arabs (SUD), Rashaayda Bedouins (RAS), Beja Hadendowa (BEJ), Nubians (NUB), Daza (DAZ), Baggara Arabs (BAG), Maba (MAB), Dangaléat (DAN), Mossi (MOS), Gurunsi Kassena (GRS) and Gourmantché (GOU)) following distinct lifestyles as sedentary farmers, semi‐nomadic or nomadic pastoralists across the Sahel (Sudan, Chad and Burkina Faso) and specifically HLA‐typed for this study ( Sahel set hereafter, Table ), plus 29 population samples from published sources (Assane et al., ; Cao et al., ; Galgani et al., ; Gomez‐Casado et al., ; Gourraud et al., ; Hajjej et al., ; Mack & Erlich, ; Mahfoudh et al., ; Modiano et al., ; Norman et al., ; Nunes et al., ; Piancatelli et al., ; Riccio et al., ; Sanchez‐Mazas, ; Sanchez‐Mazas & Tiercy, ; Spinola, Bruges‐Armas, Middleton, & Brehm, ; Testi et al., ; Torimiro et al., ). These 40 populations (Table ) are distributed among 19 countries of Eastern (ESAFR), Central (CSAFR), Western (WSAFR) and Southern (SSAFR) sub‐Saharan Africa as well as of North Africa (NAFR), and speak languages belonging to three of the four main African linguistic families, that is, Niger‐Congo (NC), Afro‐Asiatic (AA) and Nilo‐Saharan (NS) (Lewis et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…In humans, the MHC genes are found within a genomic region that spans approximately 4 Mb (Trowsdale & Knight, 2015). The MHC genes are often tightly linked and MHC alleles have been found to be non-randomly associated within haplotypes, suggesting that selection acts on multi-locus MHC haplotypes rather than single MHC genes (Begovich et al, 1992(Begovich et al, , 2001Buhler, Nunes, & Sanchez-Mazas, 2016;Hollenbach et al, 2001;Kaufman, 1999;Testi et al, 2015). In MHC studies, the heterozygote advantage hypothesis is often used to describe the principle that individuals with two different maternally and paternally inherited MHC alleles should be able to recognize antigens from a larger range of pathogens, than individuals with two identical MHC alleles (Doherty & Zinkernagel, 1975;Hughes & Nei, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the analysis of the Mandenka population is particularly motivating because it lives in a region where several infectious diseases are highly prevalent. In addition, although sub-Saharan African populations, which represent more than 2000 ethno-linguistic groups, 38 have been extensively studied for different genetic markers [39][40][41][42][43][44] including HLA, 29,[45][46][47][48] to our knowledge their HLA molecular variability has not been analysed so far at its greatest degree of detail, that is, the nucleotide level. In this study, we thus investigated the nucleotide polymorphism of 8 extended HLA genes in a sample of the Mandenka population by using full-gene NGS-MiSeq high-throughput sequencing.…”
Section: Introductionmentioning
confidence: 99%